PEMIKIRAN HAMKA TENTANG KONSEP PENDIDIKAN ISLAM - Puadi, Hairul; Nur Qomari (LPPI Universitas Al-Qolam Malang, 2019)
Islamic education is the development of the mind, structuring behavior, emotional arrangements, and human relations in the world that allows his life in accordance with Islamic ideology. The aim is to achieve the qualities mentioned by the Qur'an and Hadith. This research is a research library research, then the data collection technique used in this research is literary data collection, namely by collecting coherent library materials with a research focus. The results of the study, namely that Hamka showed a harmonious relevance between religious and public sciences. The existence of religion is not only legitimizing the existing social system, but also needs to pay attention and control human behavior well.